STUDI QUR’AN AL-MAKKI WA AL-MADANI - Titin Hardianti; Nasrullah Bin Sapa; Halimah Basri (CV. Adiba Aisha Amira, 2025)
This study examines the characteristics and differences between Makiyah and Madaniah verses in the Qur'an, as well as their implications for interpretation. This classification is essential as it serves as a guide for interpreters to understand the social, cultural, and historical contexts of revelation. The Makiyah verses were generally revealed before the Prophet Muhammad (PBUH) migrated to Medina, during a time when Islam faced significant challenges and opposition from the polytheists of Mecca. These verses tend to be brief, concise, and poetic, aiming to capture attention and touch hearts. The primary themes presented include monotheism, faith, and the stories of previous prophets. In contrast, the Madaniah verses were revealed after the migration, when Islam had gained wider acceptance and the need for social, economic, and legal regulations emerged among the Muslims in Medina. These verses are typically longer and provide detailed explanations regarding Islamic laws, interpersonal relationships, and social order. These characteristics reflect the development and maturity of the Muslim community, which required more structured guidance. By identifying these distinctions, this study provides deeper insight into the background of Makiyah and Madaniah verses, helping Qur'anic interpreters apply the contextual background of revelations more accurately in contemporary interpretations